Analisis Pengaruh Kualitas Layanan SIJARU FISIP UI terhadap Kepuasan Pengguna: Menggunakan Metode Webqual 4.0 - Firmansyah Ruspandi; Eva Rahmawati; Sri Diantika (Asosiasi Riset Ilmu Matematika dan Sains Indonesia, 2026)
The Room Reservation Information System (SIJARU) is a crucial facility in supporting academic operations at FISIP UI. However, the effectiveness and service quality of this system need periodic evaluation to ensure user satisfaction. This study aims to analyze the influence of SIJARU's service quality on user satisfaction using the WebQual 4.0 method, which includes dimensions of usability, information quality, and service interaction quality. This study employed a quantitative approach with a survey of 100 respondents consisting of students, lecturers, and educational staff at FISIP UI. Data were processed using multiple linear regression techniques, preceded by validity, reliability, and classical assumption tests. The results indicate that usability, information quality, and service interaction quality simultaneously have a significant positive influence on user satisfaction, with an Adjusted R Square value of 92.7%. The conclusion of this study is that the service quality of SIJARU has provided high satisfaction to users; however, continuous system maintenance and development are required to maintain and improve service quality in the future.